Experimental study of internal and external short circuits of commercial automotive pouch lithium-ion cells. (April 2018) - Abaza, Ahmed; Ferrari, Stefania; Wong, Hin Kwan; Lyness, Chris; Moore, Andy; Weaving, Julia; Blanco-Martin, Maria; Dashwood, Richard; Bhagat, Rohit
Highlights: The nail material affects the outcome of nail penetration test. Nail penetration test suffers from poor reproducibility. The cell behaviour during nail penetration and external short circuit can be compared. Poor reproducibility of nail penetration is attributed to the variation in contact resistance between the nail and cell. Abstract: In order to develop a deeper understanding of the behaviour of commercial automotive lithium-ion pouch cells under short-circuiting conditions, two scenarios were experimentally investigated and compared. Firstly, experiments were conducted by internally shorting 15 Ah cells by full nail penetration using three different nail materials; copper, steel and plastic. A second set of experiments involved externally shorting the cell tabs using an external circuit with a range of resistance values. In both scenarios the cell electrical and thermal response were determined by the shorting resistance. In the case of nail penetration there was a clear distinction between the outcome of the conducting and non-conducting nails, although the outcome using conducting nails suffered from poor reproducibility. The poor reproducibility was attributed to the variation in the contact resistance between the nail and the cell layers. Correlating the outcome of both tests can be used to estimate the shorting resistance and construct the current profile during nail penetration test.